An Analysis of the Types of Feedback Provided by the Lecturers: Students’ Perceived - Meutia, Cut Intan; Wiandari, Fadhillah; Sartika, Indah (Talenta Publisher, 2024)
This study aims to learn more about lecturers' different types of providing feedback to students. A qualitative-descriptive analysis was carried out to apply it. Questionnaire was used to collect the information, and its goal was to determine how the English lecturer gives feedback to students in learning the language. The researcher found that English lecturers used many different kinds of feedback during this research, which refers to Wulandary’s (2017) and Ellis’ (2017) theory. They made use of each sort of feedback. However, it should be solicited in the first place. In addition, the lecturers provided students with written suggestions regarding how they might improve. The first is the amount of direct corrective feedback, which was the highest. When students write something wrong in English class, their lecturers will give them immediate feedback through written comments.